The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/economies8030054
|View full text |Cite
|
Sign up to set email alerts
|

Trade Balance Effects on Economic Growth: Evidence from European Union Countries

Abstract: A growing number of recent research analyse the trade balance impact on economic growth. However, ambiguous results of studies imply the need for the research as the deteriorating trade balance hinders economic growth. This research aims to investigate the impact of the trade balance on economic growth as well as to evaluate it during the periods of trade deficit. Our estimations are based on the European Union (EU) 28 countries panel data over the period of 1998–2018, using the OLS method of multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
(66 reference statements)
6
29
0
Order By: Relevance
“…Trade balance rise by one percent results in approximately 0.8 percent fall in growth (segment one) and a one percent rise in trade balance results in approximately 0.7 percent fall in growth (segment two). This is also in line with studies by Blavasciunaite et al (2020); Mohammad and Sherif (2015). This also implies that though the volume of trade in West Africa may have increase over the years, however, growing trade deficits act as a drag on the economy particularly when the deficits are as a result of increase imports of consumer goods that can be produced domestically which is often the case with most countries in West Africa owing to weak productivity base.…”
Section: Model Estimation Resultssupporting
confidence: 92%
“…Trade balance rise by one percent results in approximately 0.8 percent fall in growth (segment one) and a one percent rise in trade balance results in approximately 0.7 percent fall in growth (segment two). This is also in line with studies by Blavasciunaite et al (2020); Mohammad and Sherif (2015). This also implies that though the volume of trade in West Africa may have increase over the years, however, growing trade deficits act as a drag on the economy particularly when the deficits are as a result of increase imports of consumer goods that can be produced domestically which is often the case with most countries in West Africa owing to weak productivity base.…”
Section: Model Estimation Resultssupporting
confidence: 92%
“…Revealed positive effect of net export growth on the economic performance corresponds with the findings of Cetin (2016) and Awokuse (2007), but it is contradicted by results in other EU countries, as Blavasciunaite et al (2020) discovered.…”
Section: Verification Of Research Hypotheses and Discussionsupporting
confidence: 55%
“…It was found that the growth rate of the volume of trade is positively related to a growth rate of per capita GDP and both international trade volume and trade structure toward high-tech exports result in positive effects on China's regional productivity. Trade balance effects on economic growth in European Union countries were analyzed by Blavasciunaite et al (2020) using the OLS method of multivariate regression analysis. The results indicated the negative impact of a trade balance on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding the primary commodities and characteristics that stand out; 3) Measuring changes in the prices of primary commodities before and after the pandemic in Kalimantan Barat. This issue is significant to study because a trade balance surplus or deficit can affect economic growth in a region (Blavasciunaite et al, 2020). The results of this study will be helpful for the Kalimantan Barat local government notice policies that will impact Kalimantan Barat's economic growth and the steps that need to be taken to continue improving Kalimantan Barat's trade balance performance.…”
Section: Introductionmentioning
confidence: 94%
“…The value of imports and exports of non-oil and gas has a significant adverse impact on the volatility of foreign exchange reserves (Asyaria, Budiantoro & Herianingrum, 2020). The characteristics of trade balance have shown a link to economic growth (Blavasciunaite, Garsviene & Matuzeviciute, 2020), exports, imports, and economic openness significantly affect Human Development Index (Azzaki, 2021).…”
Section: Introductionmentioning
confidence: 99%